Neurological Symptom Improvement After Re-Irradiation in Patients With Diffuse Intrinsic Pontine Glioma: A Retrospective Analysis of the SIOP-E-HGG/DIPG Project - Chavaz, Lara; Janssens, Geert O.; Bolle, Stephanie; Mandeville, Henry; Ramos-Albiac, Monica; Van Beek, Karen; Benghiat, Helen; Hoeben, Bianca; Morales La Madrid, Andres; Seidel, Clemens; Kortmann, Rolf-Dieter; Hargrave, Darren; et al. (Frontiers in Oncology, 2022)
Purpose To investigate the spectrum of neurological triad improvement in patients with diffuse intrinsic pontine glioma (DIPG) treated by re-irradiation (re-RT) at first progression. Methods Re-analysis of the SIOP-E retrospective DIPG cohort by investigating the clinical benefits after re-RT with focus on the neurological triad (cranial nerve deficits, ataxia, and long tract signs). Patients were divided as "responding" or "non-responding" to re-RT. To assess the interdependence between patients’ characteristics and clinical benefits we used a Chi-Square or Fisher’s Exact test. Survival according to clinical response to re-RT was calculated by the Kaplan-Meier method. Results As earlier reported, 77% (n = 24/31) of patients had any clinical benefit after re-RT. Among 25/31 well documented patients, 44% (n=11/25) had improvement in cranial nerve palsies, 40% (n=10/25) in long-tract signs, 44% (11/25) in cerebellar signs. Clinical benefits were observed in at least 1, 2 or 3 out of 3 symptoms of the DIPG triad, in 64%, 40% and 24% respectively. Patients irradiated with a dose ≥ 20 Gy versus < 20 Gy may improve slightly better with regards of ataxia (67% versus 23%; P-value = 0.028). The survival from the start of re-RT to death was not different between responding and non-responding DIPG patients (P-value = 0.871). Conclusion A median re-irradiation dose of 20 Gy provides a neurological benefit in two-third of patients with an improvement of at least one symptom of the triad. DIPG patients receiving ≥20 Gy appear to improve slightly better with regards of ataxia, however we need more data to determine whether dose escalation up to 30 Gy provides additional benefit.